Short Communication: Effect of organic and inorganic fertilizers application on the earlymedium maturing soybean yield - SRI AYU DWI LESTARI; SUTRISNO SUTRISNO; HENNY KUNTYASTUTI (Nusantara Bioscience, 2018)
Lestari SAD, Sutrisno, Kuntyastuti H. 2017. Short Communication: Effect of organic and inorganic fertilizers application on the early-medium maturing soybean yield. Nusantara Bioscience 10: 1-5. Efforts to increase soybean productivity can be made with the application of organic and inorganic fertilizers. Large amounts of organic fertilizer are required to give a positive impact on soybean yield. However, this practice is deemed inefficient in terms procurement and transportation, making farmers less interested. The addition of inorganic fertilizer or the use of nutrient-rich organic fertilizer (Santap NM2) is among the solutions. The objective of this research was to formulate management techniques for organic and inorganic fertilizers application on the early-medium maturing soybean line, Lokal Jateng/Sinabung-1036, to achieve the soybean’s maximum potential yield. The research was conducted on Alfisols at Muneng Research Station, Probolinggo, and Vertisols at Ngale Research Station, Ngawi, in the dry season of 2012. The experiment was performed in a randomized complete block design with factorial, with three replications. The first factor was four doses of organic fertilizer and the second factor was four combination doses of ZA, SP-36, and KCl fertilizers. On the Alfisols of Probolinggo, Lokal Jateng/Sinabung-1036 soybean did not require additional inorganic fertilizers to achieve a yield of 2.71 t/ha, whereas on the Vertisols of Ngawi, Lokal Jateng/Sinabung-1036 soybean need 2 t /ha Santap NM2 to increase its yield from 2.60 t/ha to 2.81 t/ha.